Representations of Racism in Children of Blood and Bone by Tomi Adeyemi - Siham Hattab Hamdan, Asst. Prof.; Mohammed Qassim Hamid , Researcher (lark, 2023)
This paper explores different aspects of racism within the context of the novel Children of Blood and Bone (2018) by Tomi Adeyemi, utilizing Critical Race Theory or CRT as an analytical tool. The novel is written within the genre of Young Adult Fiction which tackles the problems of young adults. Although the events of the novel take place in a fantastical setting, they capture reality and depict the lives of black African Americans. Black African Americans in the novel are represented by the oppressed minority who are the diviners. Critical Race Theory recognizes that the legacy of slavery and the racial subordination of black Americans are not only socially inherent within the non-black society but they are still covert in the legal and caste system. The novel is analyzed according to the five tenets of Critical Race Theory which can be listed as follows: Race is a social construct, Racism is ordinary, Intersectionality, Interests convergence, and Counter-Storytelling. These five basic tenets will be examined thoroughly in the paper in relation to the events of the novel.